# Solve this quadratic equation. x^{2} + 2x - 22 = 0

**Solution:**

Given quadratic equation is

x^{2} + 2x - 22 = 0

Compare with ax^{2} + bx + c = 0

Here a = 1, b = 2, and c = -22

x = [-b ± √(b^{2} - 4ac)]/ 2a

x = [-2 ± √(2^{2} - 4(1)(-22))]/ 2(1)

x = [-2 ± √92]/ 2

x = [-2 ± 2√23]/ 2

x = -1 ± √23

II Method

x^{2} + 2x - 22 = 0

x^{2} + 2x = 22

Add 1 on both sides

x^{2} + 2x + 1 = 22 + 1

(x + 1)^{2} = 23

x + 1 = ±√23

x = -1 ± √23

## Solve this quadratic equation. x^{2} + 2x - 22 = 0

**Summary:**

Solution of the quadratic equation x^{2} + 2x - 22 = 0 is x = -1 ± √23.

Math worksheets and

visual curriculum

visual curriculum